Development of 1∶4 Scale Model Coil Cryogenic System of Defocus Magnet for 2 GeV Accelerator - ZHOU Hongji1, FU Wei1, WANG Chuan1, WANG Guobiao2, LI Jianhui3, ZHU Xiaofeng1, ZHANG Suping1, JIN Zhaojun1, LIN Jun1, WANG Yang1, CAI Hongru1, LIU Jingyuan1, JIA Yunsheng1, ZHANG Tianjue1, (Yuanzineng kexue jishu, 2025)
In order to meet the demands of megawatt-class high-power proton accelerators for various applications, such as advanced research of high brightness in fundamental physics, and long-life-time nuclear waste transmutation, a 2 GeV/6 MW fixed field alternating gradient (FFAG) accelerator has been proposed by the China Institute of Atomic Energy (CIAE). Considering the inevitable beam loss of the high-power proton beam and the thermal effect of the accelerator, a preliminary study of the high-temperature superconducting (HTS) magnet solutions for the FFAG accelerator was carried out. To demonstrate the feasibility of manufacturing a spiral-shaped HTS magnet with concave edges based on ReBCO tapes, a 1∶4 scaled HTS magnet was currently being developed at CIAE. Considering the required magnetic field, the working current density of the superconducting strip and the energy efficiency of the refrigeration system, the optimal working point of the 1∶4 scaled HTS magnet was selected in the 30 K temperature zone. However, on the one hand, the cryogenic system for the large accelerator superconducting magnet is complex and large scale. On the other hand, there is no precedent for the cooling of large HTS magnets in the 20-30 K temperature zone. Therefore, a helium circulation cooling system for the HTS coil was developed. The refrigerator and HTS coils in this cryogenic system were housed in the same cryostat. The cryogenic system was powered by a 2 GM refrigerator, and it used a room-temperature circulating pump to circulate helium gas. The system ensured uniform temperature distribution of HTS coils. Using this system, the 1∶4 scaled HTS coil is cooled to 25.3 K. Since the cryogenic helium pipeline volume of this system is relatively small, the influence of cooling and rewarming of the HTS coil on system pressure is controllable. As there is no longer helium needed in the cooling process, the system pressure avoids to become too high after the loss of excess. The current carrying performance of the HTS coil and magnetic field characteristics of the HTS coil were tested using this system. The results show that the coil reaches the designed working current and the designed maximum magnetic field. The test results also prove the feasibility of using helium circulation to cool a large, non-insulated, and dry HTS coil in vacuum environment. This work verifies the cooling technology of the large HTS magnet in the 20-30 K region, and lays a foundation for the development of the CIAE 2 GeV/6 MW FFAG accelerator as one among the next generation of high energy and high power accelerators.